Single port laparoscopic colectomy for colonic cancer - Trung Vy Pham; Nhu Hiep Pham; Huu Thien Ho; Anh Vu Pham; Hai Thanh Phan; Thanh Xuan Nguyen; Nghiem Trung Tran; Xuan Dong Pham; Tien Nhan Van; Trung Hieu Mai (Vietnam Journal of Science, Technology and Engineering, 2017)
Objectives: The evaluation of feasibility, safety, and outcomes of single port laparoscopic colectomy (SPLC) for colonic cancer. Prospective study of 114 patients with colonic cancer (84 right side, 17 left side, and 13 sigmoid colon) who underwent SPLC between October 2010 and October 2016 in Hue Central Hospital. Results: Mean age of patients was 56.1±15.2 (25-87 years), male/female ratio was 70/44. Mean BMI was 23.5±2.2 kg/m2. Procedures included 84 right hemi-colectomies (73.7%), 17 left hemi-colectomies (14.9%), and 13 sigmoidectomies (11.4%). Six cases required additional ports, and 19 were converted to open surgery. Mean tumor size was 3.7±2.7 cm. Stage I: 6.1%; stage IIa: 43.9%; stage IIIa: 36.8%; and stage IIIc: 13.2%. Mean operation time was 160.5±75.5 min. There had been no deaths/intraoperative complications. Mean incisional length (including extraction) was 5.5±2.2 cm. Mean lymph nodes was 16.2±4.5. Mean hospital stay was 7.5±6.1 days. The surgical site infection rate was 3.5%, and 1 patient required reoperation (anastomotic leakage: 0.9%). After 32.2±7.5 (3-65 months) follow-up, there were no late surgical complication, incisional hernia, or incision metastasis. There were five local recurrences, and three patients developed liver metastasis in the open conversion group. The overall survival time after 2 years was 87.5%, and after 5 years, it was 59.4% (Kaplan-Meier). Conclusion: SPLC is feasible and safe procedure for the treatment of colon cancer. The cosmetic value is better (short incision confounded by umbilicus). Other outcomes were equivalent to conventional laparoscopy.